Rational Design of Functional Peptide–Gold Hybrid Nanomaterials for Molecular Interactions. Issue 37 (2nd August 2020) - Liu, Xiaohu; Zhang, Qingwen; Knoll, Wolfgang; Liedberg, Bo; Wang, Yi
Abstract : Gold nanoparticles (AuNPs) have been extensively used for decades in biosensing‐related development due to outstanding optical properties. Peptides, as newly realized functional biomolecules, are promising candidates of replacing antibodies, receptors, and substrates for specific molecular interactions. Both peptides and AuNPs are robust and easily synthesized at relatively low cost. Hence, peptide–AuNP‐based bio‐nano‐technological approaches have drawn increasing interest, especially in the field of molecular targeting, cell imaging, drug delivery, and therapy. Many excellent works in these areas have been reported: demonstrating novel ideas, exploring new targets, and facilitating advanced diagnostic and therapeutic technologies. Importantly, some of them also have been employed to address real practical problems, especially in remote and less privileged areas. This contribution focuses on the application of peptide–gold hybrid nanomaterials for various molecular interactions, especially in biosensing/diagnostics and cell targeting/imaging, as well as for the development of highly active antimicrobial/antifouling coating strategies. Rationally designed peptide–gold nanomaterials with functional properties are discussed along with future challenges and opportunities. Abstract : Rationally designed functional peptide–gold hybrid nanomaterials for various applications, such as biosensing, targeting, imaging, and so forth, due to their specific molecular interactions, are reviewed. With all the advantages of peptide–gold‐based interactive nano‐approaches, they are promising for future applications in the biomedical domain and beyond, especially in field testing.